1991
DOI: 10.1007/bf02750936
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal septicaemia among inborn and outborn babies in a referral hospital

Abstract: Neonatal sepsis was studied among one hundred neonates (50 hospital born and 50 outborn babies) over one year period. The incidence of neonatal septicaemia was 15.5 per 1000 live births in the hospital. Among outborn babies it accounted for 6.1% of total pediatric admissions and 43.7% of sick neonates referred from outside. Low birth weight and prematurity were important predisposing factors in both the groups. Blood culture was positive among 32% of outborn and 34% of inborn babies. Coagulase-negative Staphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 7 publications
8
28
2
Order By: Relevance
“…Similar reports have been made from other centers in Nigeria [13][14][15]. Staphylococcus aureus was the third commonest organism isolated among inborns in a study from India, next to coagulase-negative Staphylococcus aureus and Klebsiella pneumoniae [12]. It has been shown that horizontal transmission from mothers is probably the major source of Staphylococcus aureus to neonates [16].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar reports have been made from other centers in Nigeria [13][14][15]. Staphylococcus aureus was the third commonest organism isolated among inborns in a study from India, next to coagulase-negative Staphylococcus aureus and Klebsiella pneumoniae [12]. It has been shown that horizontal transmission from mothers is probably the major source of Staphylococcus aureus to neonates [16].…”
Section: Discussionsupporting
confidence: 75%
“…In developing countries, there is a wide variation in the incidence of NNS, ranging from 5.6/1,000 live births in a hospital-based study in Pakistan [11], 15.5 in a hospital in India [12], to 54.9/1,000 live births in Nigeria [13], which has been attributed to factors such as socioeconomic structure, perinatal practices, as well as a lack of infection control practices and good antibiotic protocols. The persistently low NNS rates from developed countries are mainly due to good infection control practices, including rational use of antibiotics [10].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is comparable with other reports. 15,16 A negative blood culture does not exclude sepsis and could be due to anaerobes. 17 In this study the predominant isolates was S. aureus which is in agreement with other reports.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in incidence of septicaemia in developed countries may be due to proper sanitation which has successfully diminished the infection in more affluent regions of the world. Most clinical bacteriologists failed to report polymicrobial sepsis because of misconception of contamination, ignorance of its significance or disregard for the second organism in an already positive culture (Sharma et al, 1987;Mathur et al, 1994;Mondal et al, 1991). However, there is a need to correlate the occurrence of polymicrobial sepsis with clinical outcome in septicaemia.…”
Section: Discussionmentioning
confidence: 99%